Microfilaria in urine cytology: Report of three cases with review of literature. Issue 7 (7th April 2020) - Sarangi, Jayati; Arava, Sudheer; Kumar, Hemanth
Abstract: Lymphatic filariasis is a major public health problem in the developing countries. In India, around 90% of the cases are attributed to Wuchereria bancrofti species morphologically identified as sheathed parasites with tail tip free of nuclei. Microfilariae have been described in urine specimens from patients with chylous and achylous hematuria as well as in a spectrum of other body fluids. Case reports describe their presence in aspirates from numerous neoplasms. However, their association with urothelial carcinoma in urine sediment has been rather rare with only three cases described previously. We report three cases of filariasis in urine cytology, one of which was associated with atypical urothelial cells. Our aim is to stress on the possibility of concomitant filariasis in body fluids and aspirates with other significant findings, especially in endemic areas. Identification of the same renders complete diagnosis and proper treatment to the patient.